2018
DOI: 10.1002/ana.25297
|View full text |Cite
|
Sign up to set email alerts
|

Structural signature of SCA3: From presymptomatic to late disease stages

Abstract: Structural damage in SCA3/MJD begins in the spinal cord, cerebellar peduncles, as well as substantia nigra and progresses to cerebral areas in the long term. These structural differences reveal some insights into the pathogenesis of SCA3/MJD and suggest a staging scheme to map the progression of the disease. Ann Neurol 2018;84:401-408.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
105
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(133 citation statements)
references
References 38 publications
26
105
2
Order By: Relevance
“…Previously, cross-sectional studies found abnormal fractional anisotropy (FA), axial diffusivity, and mainly radial diffusivity (RD) compared with controls. 3,12 Similarly, RD that reflects demyelination processes or axonal injury itself brought out most alterations and the largest ES in our analyses. In the study that divided groups of patients according to disease duration, authors were able to delineate a caudalrostral pattern of progression, and, in parallel, our study found changes only in infratentorial WM structures, corroborating for a "still in process" progress of CST damage.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Previously, cross-sectional studies found abnormal fractional anisotropy (FA), axial diffusivity, and mainly radial diffusivity (RD) compared with controls. 3,12 Similarly, RD that reflects demyelination processes or axonal injury itself brought out most alterations and the largest ES in our analyses. In the study that divided groups of patients according to disease duration, authors were able to delineate a caudalrostral pattern of progression, and, in parallel, our study found changes only in infratentorial WM structures, corroborating for a "still in process" progress of CST damage.…”
Section: Discussionmentioning
confidence: 61%
“…SC changes indeed take place early in the disease course. 3 In our cohort with mean disease duration of 9.1 years at baseline, it is probable that maximal SC atrophy would have occurred previously, and further additional changes would be difficult to identify.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…All animal procedures were approved by the University of Michigan Committee on the Use and Care of Animals (Protocol PRO00003836) and by the University of Minnesota Institutional Animal Care and Use Committee (Protocol # 1207A17510). Groups of Q84/Q84 (N=14 (7 females, 7 males), [9][10][11][12][13][14][15][16][17] month-old) and their littermate non-transgenic (wt) mice (N=11 (7 females, 4 males), 11-18 month-old), and Q135 (N= 9 (3 females, 6 males), 8-16 month-old) and their wt littermates (N=8 (5 females, 3 males), 10-16 month-old) in the C57Bl6/J background (Supplementary Table 1) were scanned. Mice were housed in cages with corncob bedding with a maximum number of five animals (range 3-5) and maintained in a standard 12-hours light/dark cycle with food and water ad libitum.…”
Section: Experimental Designmentioning
confidence: 99%
“…Machado-Joseph disease (MJD) or spinocerebellar ataxia type 3 (SCA3) is a polyQ disease caused by an expanded CAG repeat in the ATXN3 gene 12 that leads to selective dysfunction and loss of neurons of specific nuclei in the cerebellum, brain stem, midbrain, spinal cord, and peripheral nerves [9][10][11][13][14][15][16][17][18][19][20][21] . This central and peripheral nervous system pathology manifests in patients with SCA3 as ataxia and a variable degree of other symptoms, such as extrapyramidal signs, neuropathy, ophthalmoplegia, visual impairment and muscle atrophy [22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%